PENGARUH PENDEKATAN KONTEKSTUAL BERBASIS E-LEARNING ZOOM CLOUD MEETING TERHADAP PEMAHAMAN KONSEP RADIASI BENDA HITAM MAHASISWA - Ilyas Ilyas; An Nisaa Al Mu’min Liu; Antonia Fransiska Laka (Program Studi Pendidikan Fisika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Flores, 2022)
This study aims to determine the effect of a contextual approach based on e-learning on the understanding of the concept of black body radiation students of the Physics Education Study Program at the University of Flores. This type of research is quantitative research, with descriptive statistical analysis and inferential statistics to describe data on understanding the concept of black body radiation for students of the Physics Education Study Program at the University of Flores in quantum physics courses using a contextual approach based on e-learning. The data collection technique used in this research is a test technique. From the results of descriptive analysis shows that the average student learning outcomes are 79.80 which is in the sufficient category. While the results of inferential statistics show the t-count value of 5, 378, sig(2-tailed) 0.000. Because the value of sig(2-tailed) 0.000 is smaller than 0.05, this indicates that the contextual approach based on e-learning has an effect on understanding the concept of black body radiation for students of the Physics Education Study Program, University of Flores.